Effects of hydrocortisone and aminophylline on the aggregation of equine platelets in vitro - Casella, Stefania (The Korean Society of Veterinary Science, 2011)
The purpose of this study was to evaluate in vitro the effects of hydrocortisone and aminophylline on adenosine diphosphate (ADP)-induced platelet aggregation in horses. Blood samples from 30 healthy Thoroughbred horses were collected by via jugular venipuncture to assess platelet aggregation. Platelet-rich and platelet-poor plasma were prepared from all samples by centrifugation and divided into three different aliquots. In the first aliquot, platelet aggregation was measured after platelet activation with 1 µM and 0.5 µM ADP (Group A). In the other two aliquots, the effect of a 10 min preincubation with hydrocortisone (Group B) or aminophylline (Group C) on ADP-induced aggregation at final ADP concentrations of 1 µM and 0.5 µM was observed. Platelet aggregation, recorded by an aggregometer, was evaluated by measuring the maximum degree of platelet aggregation and the initial velocities of platelet aggregation were obtained. Our results demonstrated the inhibitory effect of hydrocortisone and the induction effect of aminophylline on equine platelet responses in vitro.